Spontaneous Mobilization and the Transformation of Collective Formations on the Internet: A Case Study of the PEGIDA Movement - Nam, Sang-hui (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2016)
In this article, I address with the question of how a social movement resulting from spontaneous mobilization can develop on the Internet as a collective formation. Since, as a rule, spontaneous movements possess weak collective identity, they have previously been regarded mainly as transitory phenomena. Many studies focus on the consequences of spontaneous mobilization, and above all on the question of how it may grow into a sustainable movement. Collective formation itself has so far remained more or less an unknown factor. My present study focuses on the following research questions: 1. How are collective formations of spontaneous protesters represented and generated? 2. How do they change in the course of mobilization? The empirical analysis concentrates on online comments that play an increasingly more important role for social movements and processes of spontaneous mobilization. Taking "Patriotic Europeans Against the Islamization of the West" (PEGIDA) as an example, I look into the construction of a collective formation in live comments accompanying live transmissions of PEGIDA demonstrations and their change in three stages of PEGIDA mobilization: emergence and development, stagnation and stabilization, and reactivation and differentiation. The first step explains the socio-technical foundations of collective action on the Internet. The second step focuses on the methodical approach. The third step analyzes selected text passages from online comments and describes the transformation of collective formations. URN: http://nbn-resolving.de/urn:nbn:de:0114-fqs170138